DIVERSITY INDICES OF SELECTED MACROBENTHOS IN KARANJA CREEK (DISTRICT- RAIGAD), MAHARASHTRA, WEST COAST OF INDIA - Pawar, Prabhakar R.; Kulkarni, Balasaheb G. (Journal of Indian Fisheries Association, 2007)
The diversity indices can be used as a good measure fo:r studying the effect of industrial pollution because industrial wastes and sewage almost always :reduce the diversity of natural systems into which they a:re discharged. A measurement of diversity often provides a better index of pollution than a direct measurement of pollutants. The assessment of macrobenthos diversity with :respect to diversity indices :reflects the marine population and habitat disturbance, and also serves asan important indicator of environmental conditions. The present study was designed to investigate the diversity indices of selected macrobenthos at two ecologically distinct locations on the Ka:ranj a c:reek (District - Raigad), Maha:rasht:ra, west coast of India. Results on various diversity indices like Index of Frequency (F) o:r Importance Probability (Pi), Index of Dominance (c), Rarity Index (R), Shannon's Index of General Diversity (H1 ), Ma:rgalers Richness Index (R1) and Evenness Index (e) did not va:ry significantly. This demonstrates that at present, Ka:ranja c:reek ha:rbou:rs varied fo:rms of mac:robenthic community showing no effect of human disturbance, but in future, measures must be taken fo:rthe protection and conservation ofmac:robenthic community of the c:reek.Keywords: Diversity indices, conservation, macrobenthos, container freight stations, J awaha:rlal N eh:ru Po:rt Trust